(untitled) (Bangladesh Heart Journal, 2016)
Heart valve abnormalities are the most frequent cardiac manifestations in patients with antiphospholipid syndrome (APS) with or without systemic lupus erythrematosus (SLE) though clinically significant valvulopathy occurs rarely. Here, we present a case of a 20-year-old young lady presenting with intermittent fever and polyarthralgia for 2 weeks, breathlessness for 1 week and bilateral leg swelling for 3 days. On examination, moderate anaemia, high blood pressure, generalized lymphadenopathy and evidence of mitral regurgitation was found. She had Hb% 8.5 gm/dl with high ESR. In Doppler echocardiography, there was MVP with mitral regurgitation (MR) grade III. Transeosophageal echocardiography revealed features of type A Libman- Sacks (LS) endocarditis along with MVP and MR. Unfortunately; she had strongly positive ANA, positive anti ds-DNA, positive direct coombs test & positive antiphospholipid antibody (aPL) IgG with low C3 level & proteinuria. On the basis of clinical presentation and laboratory reports, a diagnosis of SLE with secondary antiphospholipid syndrome (APS) with LS endocarditis with secondary MVP with coombs positive haemolytic anaemia was made. For treatment purpose, she was transferred to the department of Rheumatology. After 1 month during her follow-up visit, she was improved clinically & echocardiogracally. Bangladesh Heart Journal 2015; 30(1) : 33-36